School canteen food ordering application with food allergy alert feature: Malaysia perspective - Law, Check Yee; Sek, Yong Wee; Tay, Choo Chuan; Liew, Tze Hui (2023)
School canteen is one of the indispensable educational resources and plays an important role in one’s school life. As the school canteen supplies on average of a third of a student’s daily food consumption, it has a great influence on student health and nutrition. This means the school canteen plays an important role in instilling healthy eating culture among the students. Besides that, school canteen should also consider food allergy issue as the allergic reaction is unpredictable. In addition, the outbreak of pandemic COVID-19 has changed the normal practice of a school canteen. The class teachers are assigned to manually take food orders from the students or the parents. This has drastically increased the teachers’ workload. In view of these concerns, an Android-based mobile application is designed and developed to facilitate the food ordering process in the school canteen with food allergy alert feature. This can ease a class teacher’s workload and helps the school authorities to manage the school canteen especially during the recess time. It also provides a communication channel between the school canteen caterer and parents for food ordering and allergy-causing food information.